Frontier Nursing Service, Inc., Washington Committee records - Frontier Nursing Service, Inc. Washington Committee
Correspondence, minutes, membership rosters, invitations, and other printed matter documenting the fund-raising activities of the Washington Committee.
Washington Committee of the Frontier Nursing Service, an organization founded in 1925 by Mary Breckinridge and based in Wendover, Kentucky, providing family-centered, rural health care to patients in and around Leslie County, Kentucky, as well as the United States and the world, through the efforts of graduates of the Frontier School of Midwifery and Family Nursing.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Breckinridge, Mary, -- 1881-1965.; Frontier Nursing Service, inc. -- Finance; Family services -- Finance; Fund raising -- United States; Rural health services -- Finance